Modifiable factors and genetic predisposition associated with gallbladder cancer: a concise review - Liebe, Roman (Journal of gastrointestinal and liver diseases, 2015)
Gallbladder cancer (GbCa) is the most frequent malignancy of the biliary tract. It is also the 6th most common gastrointestinal tumor. It is associated with very high lethality, mainly due to the lack of symptoms up to a very late and thus incurable state. As many as 80% of patients are diagnosed at very late stages of disease, which allow only palliative therapy. As a result, most of the patients with GbCa will die within 6 months of the diagnosis, hence the average 5-year survival does not exceed 5%. Currently, surgical resection represents the only curative option in GbCa, but this approach is feasible only at an early stage of the disease. Other oncologic therapies are of limited use. The incidence of GbCa is remarkably increased in certain populations such as Native North Americans, South Indian females and, in Europe, in the Polish population. It is not clear to date if these enhanced risk populations are the result of common environmental exposure or of shared genetic risk factors. In this review we provide an overview of the state-of-art in GbCa research with the focus on the current knowledge concerning genetic and environmental triggers of this tumor.
Gesehen am 26.11.2108